Relationship between plant nutrition and severity of damage caused by white rot desease on onion (Allium cepa) Relación entre la nutrición mineral y la severidad del daño ocasionado por pudrición blanca en cebolla de bulbo - Piraneque G Nelson Virgilio; Menjivar F Juan Carlos; Aguirre Sonia Esperanza (Acta Agronómica, 2006)
In a comercial onion crop (Allium cepa) located in Tibasosa, Boyacá, Colombia, the relationship between plant nutrition and severity of damage caused by white rot disease was studied. The soil was classified as sulfic endoamept. At 20 days before sowing (DAS) and at 45, 90 and 120 days after sowing soil samples and esclerotium were taken plant tissue analysis at 45, 90 and 120 DAS was carried out. Also association among soil chemical parameters and plant percentage of damage was estudied. Results showed direct relationship among cooper content in soil (r=0.71), nitrogen in leaves (r=0.46) and magnesium in leaves (r=0.66) with percentage o damage caused by S. cepivorum. Calcium content in leaves (r=0.52), boron in leaves (r=-0.49) and esclerocios in soil Elg (r=0.56) were inversely proportional to percentage of damage. The treatment with the highest percentage of damage had higher contents of N, P and S in leaves and lower K, Ca, Mg, B, Mn, Cu and Zn. Key words: Allium cepa; Sclerotium cepivorum; plant nutrition. En un cultivo comercial de cebolla de bulbo (Allium cepa) situado en el municipio de Tibasosa, Boyacá-Colombia, se recolectaron muestras de suelos (sulfic endoaquepts) yesclerocios 20 días antes de la siembra, 45, 90 y 120 días después de la siembra (DDS); los análisis de tejidos se realizaron a los 45, 90 y 120 DDS. Se determinó la asociación entre parámetros químicos del suelo y de la planta con el porcentaje de daño. Se estableció asociación directa entre las variables, contenido de cobre en suelo Cu (r=0.71), nitrógeno foliar Nf(r=0.46) y magnesio foliar Mgf (r=0.66) con el porcentaje de daño causado por S. cepivorum. El contenido de calcio foliar Caf (r=-0.52), boro foliar Bf (r=-0.49) y esclerocios por gramo de suelo ES/g (r=-0.56) fueron inversamente proporcionales con el porcentaje de daño. El tratamiento con mayor porcentaje de daño presentó contenidos altos de N, P y S en tejidos y menores contenidos en K, Ca, Mg, B, Mn, Cu y Zn. Palabras clave: Allium cepa; Sclerotium cepivorum; nutrición de las plantas; tolerancia.